FACTORS AFFECTING THE FINANCIAL STABILITY OF AN ORGANIZATION - Nao‘betova Ziyada (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines the main factors influencing the financial stability of an organization. A systematic analysis of external and internal factors shaping the level of financial stability of business entities in modern economic conditions is carried out. Particular attention is paid to the impact of inflationary processes, instability of the foreign exchange market, changes in the tax system, as well as internal issues related to capital structure, accounts receivable, and the efficiency of asset utilization. The study reveals that the financial stability of an organization is formed under the influence of a complex of interrelated factors requiring constant monitoring and effective management. The necessity of a comprehensive approach to assessing financial stability in an unstable economic environment is substantiated.